Prevalence and influencing factors of medication-related burden among patients with late-life depression in typical city of eastern China: a cross-sectional study - Dan Liu; Linghe Qiu; Lu Han; Yajing Wang; Fei Wang; Xiaowei Liu; Jianhong Wu (BMC Public Health)
Abstract Aim To evaluate the medication-related burden (MRB) of patients with late-life depression (LLD) and its influencing factors in China using the Living with Medicines Questionnaire-3 (LMQ-3), providing reference for reducing the MRB of those patients. Method A cross-sectional study was conducted between September 2023 and January 2024 on 588 patients with LLD. LMQ-3 and MRB factors questionnaire were used for data collection. The distribution of variables was assessed using descriptive analysis, while analyses of Mann-Whitney and Kruskal-Wallis were performed to evaluate inter-group differences. To explore the MRB among patients with LLD and influencing factors, multiple linear regression analysis was performed. Results The median (IQR) LMQ-3 score of 588 participants was 102 (18), indicating a moderate MRB level. Regression analysis revealed a significant trend toward higher perceived burden among patients aged 70–79 years old, living in rural areas, receiving more medical insurance settlements, using all cash, taking more than 5 drugs each time, and taking medicine more than 3 times a day (p < 0.05), which were risk factors for higher MRB. Conversely, patients who lived with their children, had an annual household income (including adult children) more than 50,000 Chinese Yuan, and no adverse drug reactions had lower LMQ-3 scores (p < 0.05), which were protective factors. Patients’ concerns about medicine, their lack of autonomy in medicine regimens, and the lack of communication between patients and doctors on treatment regimens were the main causes of the burden. Conclusions Results of this study provided preliminary evidence of the MRB among patients with LLD. Age, residence, living status, annual household income, type of drug payment, quantity and frequency of medication, and adverse reactions significantly affected the perceived medication burden. It is advisable for health policy makers and health care providers to implement appropriate intervention strategies and burden reduction programs for this vulnerable group.